2007
DOI: 10.1097/01.aids.0000255084.69846.97
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected sex in regular partnerships among homosexual men living with HIV: a comparison between sero-nonconcordant and seroconcordant couples (ANRS-EN12-VESPA Study)

Abstract: A limited number of sero-nonconcordant homosexual couples persist in reporting risky sexual behaviour. Prevention messages should encourage communication and HIV disclosure. The relationship between unprotected sex with both casual and regular partners also calls attention about the underlying psycho-social and interactional factors that may influence sexual behaviours of people living with HIV in regular relationships, independently of the status of the partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
3
30
0
7
Order By: Relevance
“…3 Many studies on sexual behaviors of HIV-positive persons suggest that the HIV status of an HIV-positive person's sex partner is one of the factors that might influence their sexual behavior. [4][5][6][7][8][9][10][11][12][13][14][15] The findings from these studies suggest that in some populations, HIV-positive persons may be adopting serosorting, in which unprotected sexual encounters are limited to partners who have the same HIV status.…”
Section: Introductionmentioning
confidence: 89%
“…3 Many studies on sexual behaviors of HIV-positive persons suggest that the HIV status of an HIV-positive person's sex partner is one of the factors that might influence their sexual behavior. [4][5][6][7][8][9][10][11][12][13][14][15] The findings from these studies suggest that in some populations, HIV-positive persons may be adopting serosorting, in which unprotected sexual encounters are limited to partners who have the same HIV status.…”
Section: Introductionmentioning
confidence: 89%
“…10 As a result, partner HIV serostatus is often a determining factor in sexual risk decision making. 11,12 Multiple caveats to serosorting do exist. For uninfected persons, the effectiveness of serosorting relies on complete and open HIV status disclosure among monogamous men.…”
Section: Introductionmentioning
confidence: 99%
“…The number of drinks on a typical drinking day was positively associated with unprotected sex in 321 methamphetamineusing, HIV-positive MSM (p<0.05) (Semple et al, 2010). In a sample of 478 AIDS-positive MSM, Bouhnik et al, (2007) found that unprotected sex with casual partners was widespread, and it was even more frequent with main partners than it is with casual partners, putting the regular partner at risk of HIV-infection. In comparison to their American counterparts, French MSM are more prone to unprotected sero-discordant sex following binge drinking (Bouhnik et al, 2007).…”
Section: Men Who Have Sex With Menmentioning
confidence: 88%
“…In a sample of 478 AIDS-positive MSM, Bouhnik et al, (2007) found that unprotected sex with casual partners was widespread, and it was even more frequent with main partners than it is with casual partners, putting the regular partner at risk of HIV-infection. In comparison to their American counterparts, French MSM are more prone to unprotected sero-discordant sex following binge drinking (Bouhnik et al, 2007). While protected sex is higher with casual partners than with regular partners, further evidence that alcohol consumption still lowers the likelihood of protected sex with a casual partner is provided by Folch et al (2009).…”
Section: Men Who Have Sex With Menmentioning
confidence: 99%
See 1 more Smart Citation